Effect of plant adaptogens on piglets and sows - A. A. Ivanovsky; N. P. Timofeev; S. A. Ermolina (Аграрная наука Евро-Северо-Востока)
The effect of Phytoplus on weaned piglets was studied for the period of 50 days in 2018 and the influence of Algasol preparation on pregnant sows was investigated during 60 days in 2017. Phytoplus contains extracts from Rhaponticum carthamoides, Serratula coronate, and Filipendula ulmaria plants. It was administered daily, against the background of the control, into the diet of piglets aged from 40 to 90 days (n = 50 in the group): group No. 1 ‒ 0.3 g; group No. 2 ‒ 0.5 g; group No. 3 ‒ 1 gram per head per day. When Phytoplus was used, livability of piglets in all groups was 100%, the incidence in the experimental groups (2.3±0.3 heads) was 1.6-2.5 times lower than in the control group (5 heads). The live weight in the experimental groups (48,3±5,9 ‒ 51,4±7,5 кг) exceeded the result in the control group (41.8 kg) by 15-22%, and the intensity of the average daily weight gain by 24-33% (764,0±3,0 g ‒ 818,0±4,3 g against 616±2,2 g). Significant difference (P <0.05) was observed in piglets of the 3rd group, where AST increased, as compared with the beginning of the experiment, by 21.3% (from 15.9±0.6 to 19.3±0.5 units / l), and ALT by 12% (from 23.3±1.1 to 26.1 ± 2.1 units / l) and in the 2nd group where ALT increased by 46% (from 17.7±1.3 to 23.9±1.3 units /l). Algasol is a preparation from the extracts of brown algae and licorice roots. The experiment was carried out on nursing sows of large white breed pigs (2 groups of 48 animals each) when farrowing and before weaning piglets at 28 days of age. Sows of the experimental group were given Algasol daily at a dose of 50 ml per head. Algasol optimized their overall condition. The sows of the experimental group yielded 2% (572 pigs) more than in the control (561 pigs), the stillbirth decreased by 8% (23 vs. 25 animals). The death rate in the experiment was 2.1 times lower than in the control (17 vs. 8 goals), and livability was 98.5%. It has been established that Phytoplus and Algasol exert influence on the adaptive-compensatory reactions in the body of piglets and sows, that is proved by an increase in weight gain, livability of the young, and rise in the milk yield of the sows.